AZAS-AZAS PEMBELAJARAN KONTEKSTUAL DALAM PERSPEKTIF ISLAM - Wirdati Wirdati; Sulaiman Sulaiman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
Due to the queries of whether the implementation of contextual teaching strategy in teaching Islamic education is in line with Al-Quran and Hadits or not, the research tries to search for the historical facts, and the relevant verses in Al-Quran and Hadits. This was a qualitative research describing whether the contextual teaching consisting of seven components have relevance and strong base in islamic tradition. The result shows the contextual teaching principles such as, constructivism, questioning, inquiry, learning community, modelling, reflection, and authentic assessment have strong relation and foundation in Al-Quran, Hadits, and Islamic history. It can be concluded that contextual teaching is applicable in teaching Islamic education.